2004
DOI: 10.1021/jo035532n
|View full text |Cite
|
Sign up to set email alerts
|

[2 + 2]-Photocycloaddition of 1,1-Diethoxyethylene to Chiral Polyfunctional 2-Cyclohexenones. Regioselectivity and π-Facial Discrimination

Abstract: The photochemical [2 + 2]-cycloadditions of 1,1-diethoxyethylene to chiral polyfunctional 2-cyclohexenones have been carried out leading to the production of highly constrained unusual alpha-amino acids with excellent regioselectivity and satisfactory yields. Theoretical calculations have been done to rationalize the observed regio- and diastereoselectivity and show that regiochemistry is determined by the relative rate of formation of the 1,4-biradical intermediates and not by the stability of these species.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 77 publications
2
13
0
Order By: Relevance
“…At the TS4(T 1 ) associated with the attack of DHP to the DHP-PIm complex, the BO value of the C2 C5 forming bond is 0. 23 is 0.03, which indicates that a significant interaction between DHP and the PIm stabilizes this intermediate. The natural atomic charges have been shared between the DHP and the PIm fragments.…”
Section: Pim-photocatalyzed Dhp Cycloadditionmentioning
confidence: 97%
See 1 more Smart Citation
“…At the TS4(T 1 ) associated with the attack of DHP to the DHP-PIm complex, the BO value of the C2 C5 forming bond is 0. 23 is 0.03, which indicates that a significant interaction between DHP and the PIm stabilizes this intermediate. The natural atomic charges have been shared between the DHP and the PIm fragments.…”
Section: Pim-photocatalyzed Dhp Cycloadditionmentioning
confidence: 97%
“…The two levels of theory used for calculations were the density functional theory (DFT) at Becke's three parameter exchange functional and correlation functional of Lee-Yang-Parr (B3LYP) [20] with the standard 6-31G* basis set [21] for the high level and the semiempirical PM3 method [22] for the low level. This methodology has been successfully applied to study structures and reaction mechanisms for the photocycloaddition between 2-cyclohexenones and 1,1-diethoxyethylene [23]. Open-shell systems have been described within a spin-unrestricted formalism.…”
Section: Computational Detailsmentioning
confidence: 99%
“…Conjugated enone molecules participate in a variety of photochemical processes, including cycloaddition, dissociation, and rearrangement . Several research groups have studied enone photochemistry computationally, employing economical methods for treating excited electronic states such as complete active-space self-consistent field theory (CASSCF) or time-depedent density functional theory (TDDFT). The computational work has shown that the lowest-energy triplet states, T (π,π*) and T ( n ,π*), typically mediate photochemistry following intersystem crossing from the initially excited S 1 ( n ,π*) state of the enone.…”
Section: Introductionmentioning
confidence: 99%
“…Computational investigations 2-10 have focused on the participation of cyclic enones, especially 2cyclohexen-1-one (2CHO, Fig. 1), 3,6,7,9 and its substituted derivatives 4,8 in these processes.…”
Section: Introductionmentioning
confidence: 99%